Comparison between Restorative Materials for Pulpotomised Deciduous Molars: A Randomized Clinical Study - Kanwalpreet Kaur; Bharat Suneja; Sunaina Jodhka; Ravinder S. Saini; Saurabh Chaturvedi; Shashit Shetty Bavabeedu; Fahad Hussain Alhamoudi; Marco Cicciù; Giuseppe Minervini (MDPI AG, 2023)
Aim: To evaluate and compare the clinical outcomes of Cention-N (CN) and stainless steel crowns (SSCs) as restorations for pulpotomised primary molars, and to study clinical and radiographic outcomes of pulpotomies restored with these materials. Methods: The study was conducted on 60 pulpotomised molars with occlusoproximal caries. These were randomly divided into two groups and restored with either stainless steel crowns or Cention-N. Clinical performance of restorations and clinical and radiographic success of pulpotomy was examined at 6, 9 and 12 months. Results: The mean scores for marginal integrity deteriorated significantly at 6, 9 and 12 months in both groups but in comparison were insignificant. The mean for proximal contact deteriorated significantly for the Cention-N group, whereas the mean for gingival health deteriorated remarkably for the stainless steel crown group at successive evaluations. No tooth in either group showed secondary caries or discomfort on biting, except for one tooth in Cention-N group which presented with secondary caries. The clinical success rate for pulpotomised molars was 100% for both groups until nine months, although this had reduced by the end of 12 months. Radiographically, the success rate was 79.3% for Cention-N, while it was 86.6% for stainless steel crowns at 12 months. There was no significant difference in clinical and radiographic success between either group. Conclusion: Cention-N and stainless steel crowns are comparable for marginal integrity. However, crowns maintain significantly better proximal contacts while Cention-N was notably better for gingival health of the restored tooth. Both materials do not show secondary caries and discomfort on biting and are comparable in clinical and radiographic success of pulpotomy at the end of one year.